2015
DOI: 10.1088/0004-637x/811/2/132
|View full text |Cite
|
Sign up to set email alerts
|

AN EXTREME METALLICITY, LARGE-SCALE OUTFLOW FROM A STAR-FORMING GALAXY ATz∼ 0.4

Abstract: We present a detailed analysis of a large-scale galactic outflow in the CGM of a massive (M h ∼ 10 12.5 M ⊙ ), star forming (∼ 6.9 M ⊙ yr −1 ), sub-L * (∼ 0.5L * B ) galaxy at z = 0.39853 that exhibits a wealth of metal-line absorption in the spectra of the background quasar Q 0122 − 003 at an impact parameter of 163 kpc. The galaxy inclination angle (i = 63 • ) and the azimuthal angle (Φ = 73 • ) imply that the QSO sightline is passing through the projected minor-axis of the galaxy. The absorption system show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
106
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 102 publications
7
106
1
Order By: Relevance
“…The breadth and strength of the O VI absorption in strong H I absorbers atz 2-3.5 are quite similar to those observed in starburst galaxies at low redshift (see, e.g., Grimes et al 2009;Tripp et al 2011;Muzahid et al 2015) Simcoe et al 2002;Muzahid et al 2012). This strongly suggests that the bulk of the strong and broad O VI associated with pLLSs and LLSs traces large-scale outflows from high-redshift starforming galaxies.…”
Section: O VI Associated With Pllss and Llsssupporting
confidence: 72%
See 1 more Smart Citation
“…The breadth and strength of the O VI absorption in strong H I absorbers atz 2-3.5 are quite similar to those observed in starburst galaxies at low redshift (see, e.g., Grimes et al 2009;Tripp et al 2011;Muzahid et al 2015) Simcoe et al 2002;Muzahid et al 2012). This strongly suggests that the bulk of the strong and broad O VI associated with pLLSs and LLSs traces large-scale outflows from high-redshift starforming galaxies.…”
Section: O VI Associated With Pllss and Llsssupporting
confidence: 72%
“…There is overlap between the low-and high-z surveys, but broad and strong O VI absorption associated with LLSs and pLLSs at < z 1 is the exception, not the norm. Only two strong H I absorbers with broad (  Dv 300 -km s 1 ) and strong O VI absorption at < z 1 have been reported so far, both associated with a massive, large-scale outflow from a massive star-forming galaxy (Tripp et al 2011;Fox et al 2013;Muzahid et al 2015). Therefore, randomly H Iselected pLLSs and LLSs at < z 1 and < < z 2.3 3.3 show a dramatic change not only in the MDF of their cool gas but also in the properties of the associated highly ionized gas.…”
Section: O VI Associated With Pllss and Llssmentioning
confidence: 99%
“…In a standard thin-shell model, the kinetic luminosity of an outflow can be expressed asĖ k = 4πµmpCΩC f NHr d v 3 , where, mp is the proton mass, µ = 1.4 accounts for the mass of helium, and CΩ and C f are, respectively, the global and local covering fractions (see Appendix C of Muzahid et al 2015a). In M13 we have shown that 40 per cent of the intermediate redshift QSOs exhibit highly ionized outflows detected via the Ne VIII absorption.…”
mentioning
confidence: 99%
“…Indeed, only two absorbers not captured with these boundary limits shown in Fig. 6 are associated each with a massive, large-scale outflow from a massive star-forming galaxy (Tripp et al 2011;Muzahid et al 2015). These two absorbers at z < 1 have ∆ v 300 km s −1 and the metallicities of the highly ionized gas and cool ionized gas are similar and super-solar.…”
Section: Lyman Limit Systems and O VImentioning
confidence: 88%
“…These two absorbers at z < 1 have ∆ v 300 km s −1 and the metallicities of the highly ionized gas and cool ionized gas are similar and super-solar. In the z < 1 sample, Fox et al (2013) also find that strong O VI absorption is not detected when the metallicity of cool gas is low; three of the four broadest and strongest systems at z < 1 happens to be three of the four most metal-rich pLLSs/LLSs in the sample, with similar properties (although not as extreme) to those of the absorbers associated with starburst galaxies (Tripp et al 2011;Muzahid et al 2015). My interpretation of the major difference in the frequency of strong and broad O VI between the low and high z pLLS/LLS surveys is that typically low-z galaxies are much more quiescent than their high redshift counterparts and, indeed, only in the comparatively rare lowz starburst galaxies can we find the extreme O VI absorption seen commonly at high z.…”
Section: Lyman Limit Systems and O VImentioning
confidence: 90%